2012
DOI: 10.3892/ol.2012.838
|View full text |Cite
|
Sign up to set email alerts
|

Small duodenal gastrointestinal stromal tumor presenting with acute bleeding misdiagnosed as hemobilia: Two case reports

Abstract: Abstract. Only 3-5% of gastrointestinal stromal tumors (GISTs) are located in the duodenum. They are associated with an increased risk of fatal gastrointestinal bleeding, which is a primary manifestation. A small GIST (less than 2 cm in size) is easily confused with a duodenal papilla. In the 2 cases presented in this study, endoscopic examination alone resulted in a misdiagnoses of hemobilia. To the best of our knowledge, this is the first case report of this type in the literature. Patient 1 is a 66-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
28

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 8 publications
0
3
0
28
Order By: Relevance
“…Wall et al reported a rare case with duodenal-jejunal intussusception (23). Lin et al described two cases with bleeding small dGISTs (<2 cm) initially misdiagnosed as hemobilia (123). A case mimicking refractory peptic ulcer treated for 8 years was also described (76), even hypercalcemia due to elevated serum calcitriol in metastatic disease as well (124).…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…Wall et al reported a rare case with duodenal-jejunal intussusception (23). Lin et al described two cases with bleeding small dGISTs (<2 cm) initially misdiagnosed as hemobilia (123). A case mimicking refractory peptic ulcer treated for 8 years was also described (76), even hypercalcemia due to elevated serum calcitriol in metastatic disease as well (124).…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…In addition, two reasons that the small bowel GISTs were relatively smaller compared with previous reports [1,10,11,14] include tumor bleeding and the timely use of the DSA procedure. Furthermore, to our knowledge, this article presents the largest DSA series of small bowel GISTs to date [13,[17][18][19][20] . Based on our DSA findings, it is not difficult to detect and make a preoperative diagnosis and to locate small bowel GISTs.…”
Section: Discussionmentioning
confidence: 99%
“…Los GIST se manifiestan clínicamente alrededor de los 60 años de edad, siendo más frecuentes en pacientes masculinos (68% a 80%) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . La localización duodenal no es común con una prevalencia de 5% 7,18 . en series de casos de GIST localizados específicamente en el duodeno la incidencia varía entre 6% y 29% 16,17,19 .…”
Section: Presentación Clínicaunclassified
“…Los GIST duodenales son relativamente infrecuentes (prevalencia 5% a 7%), sin embargo, representan 30% de todos los tumores duodenales primarios 7 . La mayoría de las publicaciones sobre GIST duodenales son reportes de casos o series de casos [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Consecuentemente, las manifestaciones clínicas, estudio y tratamiento constituyen materia de controversia.…”
Section: Introductionunclassified